Answer:
Step-by-step explanation:
a ) starting from rest , so u = o and initial kinetic energy = 0 .
Let mass of the skier = m
Kinetic energy gained = potential energy lost
= mgh = mg l sinθ
= m x 9.8 x 70 x sin 30
= 343 m
Total kinetic energy at the base = 343 m + 0 = 343 m .
b )
In this case initial kinetic energy = 1/2 m v²
= .5 x m x 2.5²
= 3.125 m
Total kinetic energy at the base
= 3.125 m + 343 m
= 346.125 m
c ) It is not surprising as energy gained due to gravitational force by the earth is enormous . So component of energy gained due to gravitational force far exceeds the initial kinetic energy . Still in a competitive event , the fractional initial kinetic energy may be the deciding factor .